Contemporary Computing 5th International Conference, IC3 2012, Noida, India, August 6-8, 2012. Proceedings - Parashar, Manish; Kaushik, Dinesh; Rana, Omer F.; Samtaney, Ravi.; Yang, Yuanyuan; Zomaya, Albert; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This volume constitutes the refereed proceedings of the 5th International Conference on Contemporary Computing, IC3 2010, held in Noida, India, in August 2011. The 42 revised full papers presented together with 7 short papers were carefully reviewed and selected from 162 submissions. The papers are organized in topical sections on: algorithm; applications; systems (hardware and software); biomedical informations; poster papers.
Algorithm -- Applications -- Systems (hardware and software) -- Biomedical informations -- Poster papers.
Keywords: Computer science; Computer Communication Networks; Computer software; Information storage and retrieval systems; Artificial intelligence; Computer Science; Computer Communication Networks; Artificial Intelligence (incl. Robotics).; Algorithm Analysis and Problem Complexity; Information Systems Applications (incl. Internet).; Information Storage and Retrieval; Computation by Abstract Devices